Orbital soft tissue surgery for patients with Treacher-Collins or Nager syndrome. A new surgical approach with early correction of soft tissue: prospective study. Issue 5 (May 2015) - Franchi, G.; Kadlub, N.; Diner, P.A.; Bandini, M.; Vazquez, M.-P.; Picard, A.
Abstract Orbitopalpebral anomalies in mandibulofacial dysostosis (Treacher-Collins syndrome) can be difficult to correct surgically and most authors recommend correction of the malar bone after the age of 8 years. We propose a new, early surgical approach for periorbital defects that involves initial implantation of autologous fat and subperiosteal malar lift with a pedicled upper eyelid flap. We prospectively studied 5 children, 3 of whom had previously had orbital reconstruction. Initial fat graft into the periorbital area was followed by a subperiosteal malar lift with lateral canthopexy, and a pedicled upper eyelid flap if needed. Two surgeons independently assessed the patients' characteristics including scleral show before and after operation, antimongoloid palpebral fissures, canthal dystopia, number 6 cleft (Tessier classification), skin quality, and surgical and ophthalmic complications. Before operation 3 patients had had ophthalmic problems. Postoperative evaluation showed improvements in scleral show, canthal dystopia, and skin quality, and correction of antimongoloid palpebral fissures and subcutaneous number 6 clefts. There were no postoperative complications. The proposed protocol gave satisfactory aesthetic and functional results in children with Treacher-Collins syndrome. We recommend that it is considered for periorbital reconstruction in all patients with a mandibulofacial deformity.